2018
DOI: 10.1002/tesq.477
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Linguistic Markers of Collaboration in Second Language Peer Interaction: A Lexico‐grammatical Approach

Abstract: Although there is consensus that collaboration refers to two or more learners working together to accomplish a task (Davin & Donato, 2013;Ohta, 2001), debate remains about how to assess collaboration. Researchers have pursued two approaches to evaluate collaboration during peer interaction: rater judgments (e.g., Ahmadi & Sedeghi, 2016;Winke, 2013) and qualitative coding of interactional patterns (e.g., Galaczi, 2008;Storch, 2002a). Largely absent, however, has been any attempt to describe the linguistic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Arguably, the present finding validates the view of peer review writing as a form of interaction that provides EFL learners with an opportunity to exchange linguistic forms and apply these forms to the practical use in academic and peer review writing (Crawford, McDonough & Brun-Mercer 2019). At the same time, it is observed in the data that in contrast to the DMs that are found exclusively in E2 and R2, there is a group of DMs which is present only in E1 and absent in R1, R2 and E2.…”
Section: E2 R2supporting
confidence: 79%
“…Arguably, the present finding validates the view of peer review writing as a form of interaction that provides EFL learners with an opportunity to exchange linguistic forms and apply these forms to the practical use in academic and peer review writing (Crawford, McDonough & Brun-Mercer 2019). At the same time, it is observed in the data that in contrast to the DMs that are found exclusively in E2 and R2, there is a group of DMs which is present only in E1 and absent in R1, R2 and E2.…”
Section: E2 R2supporting
confidence: 79%
“…This is supported by MacIntyre et al's (1998) assertion that inter-speaker relationships, including power relations, the level of intimacy, and social distance, are important elements in second/foreign language (L2/FL) communication. In terms of language learning, it has also been reported that other learners play an important role (Thomas & Rose, 2019), and that peer interactions help to improve TL proficiency (Chen, 2018;Crawford, McDonough, & Brun-Mercer, 2019). Students need to help each other more often (Dörnyei, 1997) and to exchange ideas with their classmates (Murphey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To make the interview data anonymous and to get ready for the establishment of categories, the interview data were first transcribed, translated into English, and coded. The coding categories were based on the causes of anxiety, including risk-free environments with lower stress levels (Shao et al, 2013), more seeking practices (Dewaele, Petrides, & Furnham, 2008), and more pair group work (Crawford, McDonough, & Brun-Mercer, 2019). The interview data was analyzed then to find any patterns or relationships…”
Section: Introductionmentioning
confidence: 99%